2014
DOI: 10.7314/apjcp.2014.15.19.8229
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Economic Aspects of Cervical Cancer Screening Strategies Worldwide: Discrepancy between Economic Analysis and Policymaking

Abstract: Background: Organized cervical screening has decreased the incidence of cervical cancer. However, screening strategies vary in different countries. Objectives: We performed a systematic review to evaluate the economic aspects of different screening methods. Materials and Methods: We searched databases and then data were abstracted from each study. We evaluated articles based on different types of screening tests as well as screening age and intervals, and using incremental cost effectiveness ratio via calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 63 publications
(171 reference statements)
3
30
0
Order By: Relevance
“…Persistent expression of the E6 and E7 proteins of the high-risk type HPV16 virus is a key risk factor for cervical cell transformation and the maintenance of a malignant phenotype (Gan et al, 2014;He et al, 2014), and represents the primary mechanism by which the virus escapes host cell immune surveillance after HPV infection. Thus, the immune escape mechanism of HPV has become the focus of current research (Niebler et al, 2013;Nahvijou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent expression of the E6 and E7 proteins of the high-risk type HPV16 virus is a key risk factor for cervical cell transformation and the maintenance of a malignant phenotype (Gan et al, 2014;He et al, 2014), and represents the primary mechanism by which the virus escapes host cell immune surveillance after HPV infection. Thus, the immune escape mechanism of HPV has become the focus of current research (Niebler et al, 2013;Nahvijou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a systematic review by Nahivjou and colleagues 13 of cc screening strategies from an economic standpoint suggested that hpv dna testing-starting at age 30 or older, with screening intervals of 5 years or more-was the most cost-effective strategy. They also found that, in some countries, national guidelines did not match scenarios emerging from cost-effectiveness studies.…”
Section: Discussionmentioning
confidence: 99%
“…A negative hpv dna test is associated with an 0.27% cumulative incidence rate of cervical intraepithelial neoplasia grade 3 or worse after 6 years; the rate for women with a negative cytology result is 0.97% 30 . Thus, screening intervals more frequent than 5 years are not recommended for primary hpv dna testing 4,13 . According to our model, moving from 5-yearly to triennial hpv dna testing would cost more than $100,000 per additional qaly gained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide variation in the cervical screening strategies in different countries. 24 The main variations are related to type of screening test, starting age, and screening intervals. HPV testing, Pap smear tests, and visual inspection with acetic acid (VIA), are three types of screening tests that are used for cervical screening worldwide.…”
Section: Discussionmentioning
confidence: 99%